Ants and beetles colonization on burnt and not burnt rabbit carcasses in Puncak Alam Selangor / Marjan Hananie Mazlan - Mazlan, Marjan Hananie (2015)
Forensic entomology is the application and study of insect biology to criminal matters. A study has been conducted to see the ants and beetles colonization as predators on burnt and not burnt rabbit carcasses. The study was carried out in an open area near Water Tank 1, UiTM Puncak Alam Campus Kuala Se1angor at Latitude of N 3° 12.0456' and Longitude of E 101° 26.8446'. Four male rabbits from Oryctolagus cuniculus species were used in this experimental study. In burnt case study, two rabbit carcasses were poured with petrol and served as burnt carcasses, while another two carcasses were placed in cages without any manipulation that acts as control. The control carcasses were used to see the comparison of the decomposition rate and the predators' colonization were different or otherwise. This study fmdings show that, colonization of ants on not burnt and burnt rabbit carcasses shows some different patterns. The frequency of ants visiting the not burnt rabbit carcasses is higher compare to burnt rabbit carcasses. For not burnt, ants frequency is 932 ants, while for burnt ants frequency are 723. In addition, the diversity of ants species visiting not burnt rabbit carcasses also higher than the burnt rabbit carcasses. The diversity of beetles' species also does not contain much difference between not burnt rabbit carcasses and burnt rabbit carcasses. Types of beetles' specIes were found on the carcasses were, Staphylinidae paderus species, Cicindela repanda species, Cicindela unipunctata and Melanotus communis complex species. This study had provided a new knowledge on the role and diversity of ants and beetles as predators on carcasses.